Эммануэль: роман / Эммануэль Арсан ; перевод с франнцузского Е. Л. Храмова - Арсан Эммануэль (Элита, 1992)
Экземпляры: ф.2 (1999) / Инвентарный номер: 38561 / Сис.шифр: 84(4Фра)-4 / Авт.знак: А 85 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44